The Impact of Extracurricular Sports Programs on High School Students' Discipline and Academic Achievement - Krisna, Eric (Journal of Salutare, 2025)
Extracurricular sports activities in high school have a strategic role not only in supporting physical health, but also in shaping the character of discipline and improving students' academic achievement, although a number of previous studies have confirmed the benefits of extracurricular activities, the results are still varied mainly in explaining the role of discipline as a mediator. This study aims to analyze the influence of extracurricular sports on the discipline of high school students and its implications on academic achievement with discipline as a mediator variable. The method used is Systematic Literature Review (SLR) by examining 23 articles published in 2020–2025 obtained from international databases and national journals. The results of the study show that extracurricular sports have a positive effect on student discipline which is reflected in regularity, self-regulation, motivation, happiness, and social solidarity. In addition, sports contribute to improving academic achievement both directly through concentration, physical health, time management, and learning motivation, and indirectly through discipline as a mediator. Discipline has proven to be an important variable that bridges sports involvement with student academic achievement.